COMPARATIVE ADVANTAGE OF ExPORTS OF AGRICULTURAL PRODUCTS AND FOOD AND SERBIAN DANUBE COUNTRIES - Игњатијевић, Светлана; Милојевић, Иван; Иванчевић, Саво (Economics of Agriculture, 2011)
The paper analyzes international trade in the Danube region. The case study is an analysis of comparative advantage and specialization in international trade in agricultural products, especially food Serbia and the Danube region. Dynamic structure is seen in foreign trade, comparative advantage in exports of agricultural products and food by applying methods and Balassa specialization in international trade using Grubel–Lloyd index of this. The study found a positive comparative advantage in exports of agricultural products and food, Serbia, Moldova, Hungary, Ukraine, Bulgaria and Romania, and intraindustry nature of the exports of agricultural products and food in most countries of the Danube region. The production of agricultural products and food there is the potential to be exploited to improve competitive positions in the market. The basis of competitiveness should be recognizable quality products and brands.